Praktik Pelestarian Lingkungan Melalui Kegiatan Penanaman Pohon di Kawasan Pesisir Pantai Mapak Mataram - I Made Permadi Utama; Baiq Zuhrotun Nafisah; Terasne Terasne; Ahmad Hanan; Nanang Sugianto; Imansyah Imansyah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
Mapak Indah Beach is one of the beaches that has great potential to attract both domestic and foreign tourists. However, this potential cannot be matched by the inadequate situation of the beach, on the contrary it is contrasted with all kinds of problem, one of them is the hot and arid condition. This is one of the most preferred tourists in one of the coastal tourism areas in the west of the city of Mataram. One effort to solve this problem is a tree-planting. In addition to rehabilitating land in the coastal region, this is also to increase economic value for the surrounding community. The methods are planning, preparation and planting. Planning is plans to determine the prospective location, the need for the number of seeds, and how to arrange the time. The results obtained from the tree planting program activities at Mapak Indah Beach in the District of Sekarbela are the Cemara Laut trees that try to prevent coastal abrasion, reduce aridity, and fertilize the soil. It can be used by the community and tourists or beach visitors in the future.